A METHODOLOGY FOR SIMULATION AND ASSESSMENT OF CONCENTRATED SOLAR POWER PLANTS - Starke, A. R.; Lemos, L. F. L.; Colle, S.; Reinaldo, R. F.; Cardemil, J. M.; Escobar, R. (Revista de Engenharia Térmica, 2016)
A thermal analysis of Concentrated Solar Power plants is conducted considering parabolic trough collectors (PTC), linear Fresnel collectors using direct steam generation scheme (LFC-DSG) and central receiver system using both molten nitrate salts (CRS-MNS) direct steam generation (CRS-DSG). The plant capacities were ranged from 50 to 800 MWth and the analysis focuses on the environmental conditions of selected locations in South America. Thus, the study considers a parametric analysis of the main design parameter for different plant scales, in terms of the thermal performance indicators as solar field aperture area, power block rating capacity and plant annual efficiencies. The annual production of the plants is calculated by using the Transient System Simulation program (TRNSYS), which considers a new component library developed for that purpose. This library is based in the open access models developed by the U.S National Renewable Energy Laboratory and currently employed by the System Advisor Model (SAM) program. In addition, a new fluid properties subroutine compatible with TRNSYS codes standards was developed, which uses the freeware CoolProp library. These approaches allowed to modify and create new configurations for CSP plants, e.g. thermal storage for the DSG scheme.